The Potential Used of Humic Substance As Natural Organic Additives For Ruminants: A Review - T. Suteky; Dwatmadji Dwatmadji; E. Soetrisno (Jurnal Sain Peternakan Indonesia, 2023)
Humate substances (HSs) are raw materials very easy to obtain and are naturally occurring organic molecules found in soil due to the humification of dead organic components. Traditionally used as conventional medicine in China and India and as soil fertilizer in agriculture. Humic acids are widely utilized as feed additives and could enhance ruminant performance. The effect of humic acid on feed intake depends on the level of supplementation, a humic acid source, experimental animals used and the region experimented.  Humic acid also increases the average daily gain, and sometimes increases feed digestibility and feed efficiency in goats, cows and cattle. Enhancement of milk yield, total solids, fat-corrected milk (FCM), and energy but does not influence milk composition. That supplementation also lowers blood cholesterol, excluding eosinophil and neutrophil, without affecting the haematological value. HSs also have anti-bacterial properties and HSs affect gut microbiota and rumen, such as increasing fungi counts and pH alteration, but the effect on bacteria and the protozoal population is non-consistent. In other trials, HSs have also been shown to reduce the process of methanogenesis.